Do the Th17 Cells Play a Role in the Pathogenesis of Leptospirosis? - Kanchana Bandara; Chinthika Gunasekara; Manjula Weerasekera; Chamil Marasinghe; Nilantha Ranasinghe; Neluka Fernando (Canadian Journal of Infectious Diseases and Medical Microbiology)
Objectives. The aim of this study was to determine the level of five different pro- and anti-inflammatory cytokines to study the inflammatory response of leptospirosis. Materials and methods. The serum cytokine levels of IL-10, IL-17A, IL-21, IL-23, and TNF-α were investigated in 57 patients with leptospirosis and 12 healthy controls using a commercially available ELISA kit (Mabtech, Sweden). Statistical analysis was done using Graphpad Prism. Results. Elevation of serum IL-10 and IL-17A levels and significant elevation of serum IL-21 (p=0.002), IL-23 (p=0.002), and TNF-α (p=0.039) were observed among leptospirosis patients compared to the healthy control group. The two major complications observed among these patients were renal failure and liver involvement. Renal failure was significantly associated with elevation of IL-21 and IL-23, while patients with liver involvement had a significant elevation of IL-21, IL-23, and TNF-α. Conclusion. Elevation of IL-17A together with the significant elevation of IL-21 and IL-23 suggests a possible involvement of Th17 cells in the immunopathogenesis of leptospirosis.